2005
DOI: 10.1111/j.1365-2656.2005.01002.x
|View full text |Cite
|
Sign up to set email alerts
|

Diet quality affects egg size and number but does not reduce maternal antibody transmission in Japanese quailCoturnix japonica

Abstract: Summary1. The ability to resist infection is an important component of survival and lifetime reproductive success. Mounting and maintaining an immunological defence is assumed to be energetically costly and nutritional resources expended on immune function may induce trade-offs with other energetically expensive functions, including reproduction. Resource limitation may even have transgenerational effects on immune function during reproduction because mothers are the primary source of humoral immunity in young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
54
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 46 publications
(73 reference statements)
7
54
4
Order By: Relevance
“…AICc ranking, delta values, likelihoods and weights and model r 2 for models of life-history effects on yolk IgY deposition. Analysis was done assuming a star phylogeny (OLS) and assuming stabilizing selection with drift (OU) using a tree compiled from the literature and presented in Cohen et al (2008 Grindstaff et al 2005) and comparable to estimates reported in Ficedula albicollis (0.63 mg ml 21 relative to chicken standard, Hargitai et al 2006). Several factors could contribute to the low levels measured in wild altricial birds.…”
Section: Discussionmentioning
confidence: 99%
“…AICc ranking, delta values, likelihoods and weights and model r 2 for models of life-history effects on yolk IgY deposition. Analysis was done assuming a star phylogeny (OLS) and assuming stabilizing selection with drift (OU) using a tree compiled from the literature and presented in Cohen et al (2008 Grindstaff et al 2005) and comparable to estimates reported in Ficedula albicollis (0.63 mg ml 21 relative to chicken standard, Hargitai et al 2006). Several factors could contribute to the low levels measured in wild altricial birds.…”
Section: Discussionmentioning
confidence: 99%
“…Different lowercase letters reflect statistically significant differences. and containing more nutrients and antibodies that are essential for chick survival (Galbraith, 1988;Farooq et al, 2003;Grindstaff et al, 2005). High 'quality' females may invest more in reproduction and deposit more resources into their eggs if they are to increase offspring fitness (Pilz et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Total antibody levels in the quail plasma were determined by enzyme-linked immunosorbent assay (ELISA) following the protocol set out by Grindstaff et al (Grindstaff et al, 2005). Plates were coated with anti-chicken IgY (Sigma-Aldrich, cat.…”
Section: Antibody Assaymentioning
confidence: 99%